Neuromuscular strength, not sagittal-plane joint or modeled muscle-tendon kinematics, is associated with 50-m sprint performance in youth male sprinters - Zhou, H.; Yang, J.; Lin, Z.; Zhou, C.; Liang, W. B.; Zhang, R.; Xuan, D.; Liang, W.; Huang, W. (Frontiers in Physiology, 2026)
Introduction: Maximum-velocity sprinting imposes extreme mechanical demands on the hamstring muscle-tendon unit, yet how neuromuscular function, sprint kinematics, and modeled muscle-tendon behavior jointly differentiate youth sprinters of varying performance levels remains poorly characterized. We investigated the associations among these factors and 50-m sprint performance in youth male sprinters.